2004
DOI: 10.1111/j.1442-2042.2004.00833.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of vardenafil in patients with erectile dysfunction: Result of a bridging study in Japan

Abstract: Aim : Vardenafil is a selective and highly potent phosphodiesterase type 5 (PDE5) inhibitor for the treatment of erectile dysfunction (ED), with improved selectivity for PDE5 and demonstrated efficacy for improving sexual function in men with ED. The current study investigated the safety and efficacy of this new PDE5 inhibitor in Japanese men with ED.Methods : This was a prospective, double blind, randomized clinical trial designed to evaluate the efficacy and safety of vardenafil. Following a 4-week treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…However, treatment option for difficult-to-treat ED patients, such as patients accompanying DM, has been limited in Japan, where high dose PDE5 inhibitors or intracavernosal injection/intraurethral injection of prostaglandin E1 are not approved, despite as many as 30% of ED patients failing sildenafil 50 mg. 13 Certainly, results of a phase IIb clinical study of vardenafil in Japan demonstrated its efficacy in wide range of ED population, but that study excluded enrollment of patients with DM. 15 So, it is quite important to evaluate if high doses of PDE5 inhibitor can offer the chance for difficult-to-treat ED patients, such as those with DM, to improve their erectile function. This study was planned as the first study in Japan to confirm better efficacy of high dose of vardenafil (20 mg) compared to the recommended dose of vardenafil (10 mg) in such a population with double-blinding settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, treatment option for difficult-to-treat ED patients, such as patients accompanying DM, has been limited in Japan, where high dose PDE5 inhibitors or intracavernosal injection/intraurethral injection of prostaglandin E1 are not approved, despite as many as 30% of ED patients failing sildenafil 50 mg. 13 Certainly, results of a phase IIb clinical study of vardenafil in Japan demonstrated its efficacy in wide range of ED population, but that study excluded enrollment of patients with DM. 15 So, it is quite important to evaluate if high doses of PDE5 inhibitor can offer the chance for difficult-to-treat ED patients, such as those with DM, to improve their erectile function. This study was planned as the first study in Japan to confirm better efficacy of high dose of vardenafil (20 mg) compared to the recommended dose of vardenafil (10 mg) in such a population with double-blinding settings.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of adverse drug reactions was not so different between 10 mg and 20 mg in this population, although vardenafil 20 mg showed slightly higher incidence of headache and flushing than 10 mg, which is consistent with the adverse event profile of a highly selective PDE5 inhibitor. 12,13,15,16 The majority of these events were mild in intensity and transient.…”
Section: Discussionmentioning
confidence: 99%
“…The first study, conducted between September 2001 and June 2002, assessed the safety and efficacy of vardenafil in the treatment of ED in men from Taiwan and South Korea (Taiwan, six centers; South Korea, seven centers). The second study, conducted between October 2000 and August 2001 in Japan (33 centers), has been reported previously [24]. After a 4‐week run‐in baseline period, patients were randomized to receive vardenafil (10 mg) or placebo for 12 weeks on an “as needed” basis, followed by a 7‐day follow‐up to collect safety information.…”
Section: Methodsmentioning
confidence: 99%
“…Although side effects do occur with vardenafil (most notably headache, flushing, indigestion and nasal congestion), providing that the drug is used in line with the labeling recommendations, there is no convincing evidence in the literature of any significant safety issue, including cardiovascular, visual and aural safety [105–127].…”
Section: Drugs Which Are Effective When Administered Systemicallymentioning
confidence: 99%